Ketogenic therapy in childhood and adolescence: recommendations of the Brazilian experts group - Letícia Pereira de Brito Sampaio; Adélia Maria de Miranda Henriques-Souza; Katia Lin; Lenycia de Cassya Lopes Neri; Luciana Midori Inuzuka; Ludmila Inácio de Lima Uchôa; Marcela Marques de Oliveira Gregório; Laura Maria Guilhoto; Maria Augusta Montenegro; Mariana Lunardi; Marielza Veiga; Patricia Azevedo de Lima; et al. (Arquivos de Neuro-Psiquiatria, 2023)
Ketogenic dietary therapies (KDTs) are a safe and effective treatment for pharmacoresistant epilepsy in children. There are four principal types of KDTs: the classic KD, the modified Atkins diet (MAD), the medium-chain triglyceride (MCT) diet, and the low glycemic index diet (LGID). The International Ketogenic Diet Study Group recommends managing KDTs in children with epilepsy. However, there are no guidelines that address the specific needs of the Brazilian population. Thus, the Brazilian Child Neurology Association elaborated on these recommendations with the goal of stimulating and expanding the use of the KD in Brazil.